(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Lending is the primary activity of commercial banks. As of November 1, 2025, the share of loans in total assets of commercial banks in the Republic of Uzbekistan amounted to 67.6 percentage points. This article examines the types of loans and theoretical approaches to ensuring bank liquidity amid the ongoing expansion of lending. Existing problems in the industry are identified and solutions are proposed.